Dynamic spillovers between clean energy stocks and fossil fuels: The role of climate policy uncertainty and geopolitical risk - Mubaiwa, Darren Tinotenda (University of the Witwatersrand, Johannesburg Date of Issue *, 2024)
Clean energy stocks have emerged as a means for environmentally conscious investors to support and foster the growth of companies that are involved in the green energy sector. However, given the entrenched place that non-green energy still holds, investors must contend with the reality that these clean energy stocks may be connected to fossil fuels. Therefore, the study applies the TVP-VAR model to analyze the volatility spillovers among these markets. Our empirical analyses demonstrate that there is strong connectedness between clean energy stocks and fossil fuels. Notwithstanding, we observe that the spillovers among fossil fuels (crude oil, diesel, jet fuel etc.) are stronger than the intermarket spillovers between these energy commodities and the clean energy stock market. We then proceed to examine the effect of climate policy uncertainty and geopolitical risk on these spillovers. Using the causality-in- quantiles technique of Balcilar et al. (2016), we find that both climate policy uncertainty and geopolitical risk have a formidable impact on clean energy stock and fossil fuel intermarket spillovers. Moreover, using the Quantile-on-Quantile regression approach of Sim and Zhou (2015), we find that climate policy uncertainty and geopolitical risk have heterogeneous effects across the distribution of the clean energy stock and fossil fuel spillover nexus. These findings constitute important information for investors and policymakers.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Clean energy stocks; fossil fuels; climate policy uncertainty; geopolitical risk; non-parametric techniques; SDG-13: Climate action; SDG-7: Affordable and clean energy